Perempuan dan Tasawwuf (Menakar Bias Gender dalam Kajian Sufisme) - Achmad Faesol (Jurnal Al-Hikmah, 2021)
Gender discourse in sufism tends to attract attentions. Such charm emerges due to the fact that the Sufism is originally genderless. Sufism isn't bound nor chained by gender whether it is masculinity or feminity. However, the reality displays the other way around. Therefore, the current study attempts to capture women's position in the discourse of tasawwuf. Library research is employed as the research method of this study. Although gender domination is displayed in the early academic papers of Sufism, the existance of female Sufis have been proven throughout history. In the context of Sufism, masculinity would not emerge without feminity. Such statement only proves that there is no superiority between masculinity and femininity since both display a causal relationship. The research result showed that tasawwuf is free from feminine or masculine attributes. The gender construction in tasawwuf doesn't lay on the gender of the sufi but on the degree of feminity and masculinity of their psychiatric attributes which are reflected in their behaviour and acts. In the context of sufism, masculinity, which is socially considered as something dominant, substantially has "flaw". This is because masculinity would not emerge if there's no feminity. This is a mysterious great power of feminity in Sufism discourse. In short, there is no superiority between masculinity and feminity. Both are equal and as a result of love.